Analysis of human leukocyte antigen genotypes in pemphigus with antidesmoglein antibody profile shift - Seiko Mitsui; Koji Kamiya; Yoshiki Tokura; Keiji Iwatsuki; Yumi Aoyama (Wolters Kluwer Medknow Publications, 2016)
In particular pemphigus cases, the phenotypic transition between pemphigus vulgaris and pemphigus foliaceus is observed with the change of antibody profile between anti-desmoglein (Dsg) 3 antibodies and anti-Dsg1 antibodies. In this study, we examined human leukocyte antigen (HLA) genotypes of four pemphigus patients who presented with the phenotypic transition and/or antibody profile shift. Two out of four patients possessed a DRB1*0405-DQB1*0401, and two out of four patients possessed a DRB1*1405-DQB1*0503. These alleles might be associated with the development of phenotypic transition and antibody profile shift.